Multiple-race mortality data for California, 2000-2001. - Heck, Katherine E. (Association of Schools of Public Health, 2004)
OBJECTIVES: To examine mortality rates and quality of race reporting for multiple-race individuals in California using the new multiple-race data available on the death certificate. METHODS: Death date were drawn from California vital statistics for 2000 and 2001. Denominator data were drawn from the 2000 census Modified Race Data Summary File. The authors calculated mortality rates and relative standard errors for multiple-race individuals as a whole and by county, and for the three largest reported multiple-race groups (African American and white, American Indian/Alaska Native and white, and Asian and white). RESULTS: Decedents reported to be of more than one race were disproportionately young, Hispanic, male, and never-married. Age-adjusted mortality rates for multiple-race groups were approximately one-sixth as high as rates for single-race individuals. There was substantial variability in rates for multiple-race decedents according to county of residence. CONCLUSIONS: Mortality rates for multiple-race people were implausibly low, and death certificates for multiple-race individuals were geographically clustered. Race reporting on death certificates will need to be improved before accurate death rates can be calculated for those of multiple races.